Issues on Trainability - Radak, Zsolt; Taylor, Albert W. (Frontiers in Physiology, 2022)
Trainability is an adaptive response to given exercise loads and must be localized to the targeted physiological function, since exercise- induced acute and chronic adaptations are systemic. Lack of adaptation or moderate level of adaptation in one organ or one physiological function would not mean that other organs or functions would not benefit from exercise training. The most beneficial training load could easily be different for skeletal muscle, brain, the gastro-intestinal track or the immune systems. Hence, the term of non-responders should be used with caution and just referred to a given organ, cell type, molecular signaling or function. The present paper aims to highlight some, certainly not all, issues on trainability, the specificity of trainability, and the systemic nature of exercise-induced adaptation.